Pemodelan Graf Berarah Berbobot untuk Optimasi Penentuan Rute Terpendek Antar Kampus Polimarin Berbasis Algoritma Dijkstra - Ariyani, Helena Devi; Nafillah, Khoirotun; Nindita, Kirtyana; Ngatmin, Ngatmin; Rahayu, Sri Tutie (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2026)
The mobility of academicians between the two geographically separated campuses of the Indonesian Maritime State Polytechnic (Polimarin), namely Campus 1 Ungaran and Campus 2 Bendan Duwur Semarang, creates travel efficiency issues due to numerous unmeasured route alternatives. This study aims to model the inter-campus road network as a weighted directed graph and apply the Dijkstra algorithm to determine the shortest route accurately and verifiably. The research employs an applied computational approach using actual distance data obtained from Google Maps (driving mode), collected on August 22, 2024, at 09:00 WIB to represent traffic conditions at that time. The process includes node identification (strategic locations), edge formation (connecting road segments), and weight assignment based on actual distances, resulting in a graph with 9 nodes and 10 edges. The iteration process is conducted in 8 steps by evaluating the minimum accumulated weight at each stage. The results indicate that the shortest path is A → B → E → G → H → I, passing through Jl. PTP Ngobo, Jl. Diponegoro–Jl. Slamet Riyadi, Jl. Moh. Yamin–Jl. Ahmad Yani, and Jl. Gatot Subroto, with a total distance of 25.80 km out of 11 possible routes. These findings demonstrate that the Dijkstra algorithm is effective for route optimization by eliminating inefficient paths through cumulative weight evaluation. Validation is performed by comparing the algorithm’s results with Google Maps recommendations based on travel distance. However, this study is limited to static data, and further development is required through the integration of dynamic traffic data.